Exploring the potentials of robotic inclusive education in supporting students with disabilities / Ir. Dr. Nina Korlina Madzhi ... [et al.] - Madzhi, Nina Korlina; M. Thamrin, Norashikin; Zulkifli, Zurita; Herman, Sukreen Hana (Universiti Teknologi MARA, Kedah, 2024)
Educational robotics integrates robotics with science, technology, engineering, and mathematics (STEM) in providing hands-on learning experiences using robots and related technologies. This work funded by UNESCO grants has been conducted during a 3-day program entitled “Empowering STEM-based Robotic Education in Special Needs Schools” at “Pusat Pendidikan Khas Integrasi (PPKI)” SMK Puncak Alam 3, Selangor. Thirty participants were from the ages of 13-15. 85.7% were male students and 14.3% were female students. Zoom: Bit Robot Car Kit for microbit was used during the program. Participants were placed in three groups and introduced to the main modules consisting of Maker Line Sensor and Servo & DC Motors. They were exposed to simplifying line following for beginners, which consists of Auto calibration, Line Detection LED indicator as well as Analog & Digital output signals. They also learned about motor control and creation movements as the final part of the program. Based on the findings, 93% of the participants only found out about the microbit application at the school, which is during the program itself. At the end of the program, the program achieved the conclusion that Education Robotics helps to create a synergetic learning environment for stimulating students’ motivation and collaboration among group members.